2018
DOI: 10.1002/app.47053
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced positive temperature coefficient in amorphous PS/CSPE‐MWCNT composites with low percolation threshold

Abstract: In this work, amorphous polystyrene/chlorosulfonated polyethylene composites doped with multiwalled carbon nanotubes (PS/CSPE‐MWCNT) were constructed by in situ polymerization to form semi‐interpenetrating networks. The MWCNTs showed excellent dispersion and selective location in the PS regions. High electrical conductivity and low percolation threshold (0.89 wt %) for the composites were achieved. An enhanced positive temperature coefficient (PTC) behavior for amorphous PS/CSPE‐MWCNT composites was first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Lai et al 130 prepared amorphous PTC composites with polystyrene/chlorosulfonated polyethylene (PS/CSPE) as the matrix and MWCNTs as the conductive filler by in situ polymerization, where a semi-interpenetrating network was formed in this PS/CSPE/MWCNT composite and MWCNTs were mainly dispersed in PS. A remarkable microphase separation structure of the composites was gradually observed with the increase of MWCNT content, especially when the MWCNT contents were greater than 3 wt% as shown in Fig.…”
Section: Strategies For Amorphous Polymer Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lai et al 130 prepared amorphous PTC composites with polystyrene/chlorosulfonated polyethylene (PS/CSPE) as the matrix and MWCNTs as the conductive filler by in situ polymerization, where a semi-interpenetrating network was formed in this PS/CSPE/MWCNT composite and MWCNTs were mainly dispersed in PS. A remarkable microphase separation structure of the composites was gradually observed with the increase of MWCNT content, especially when the MWCNT contents were greater than 3 wt% as shown in Fig.…”
Section: Strategies For Amorphous Polymer Matrix Compositesmentioning
confidence: 99%
“…This research fills a gap in the field of low-temperature PTC composites. [128][129][130] In addition, the Curie temperature range of this EVA/-LA/CB composite can be adjusted by the addition of a thickener of dioctyl phthalate (DOP), which is an innovative research approach in the field of PTC composites with low Curie temperature points. Different types of functional additives usually result in different effects on the PTC performance of PTC composites.…”
Section: Low-crystallinity Polymer Matrix Systems With Functional Fil...mentioning
confidence: 99%
“…When the filler content increases to the percolation threshold, the conductive network is easily influenced by external factors, resulting in an obvious change of electrical resistance of the composites. [27][28][29] The relationship between conductivity and filler content of the composites is shown in Figure 1b. With increasing CCB content, the electrical conductivity of the composites increases.…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…To overcome these drawbacks, the combination of immiscible polymer blends [35][36][37][38][39][40][41] could be an alternative strategy based on the following two factors: (i) the PTCs will be confined in the immiscible polymer with higher T m when it is manifesting PTC property and (ii) the binary polymer system has superiority to control resistance of room temperature in practical production due to the expanded ranges of percolation derived from the additional phase morphology percolation transition. Based on immiscible high density polyethylene (HDPE)/ polyvinylidene fluoride (PVDF) system, Zhang et al 37 have reported that the PTCs with "sea-island" morphology exhibited preferable PTC reproducibility.…”
Section: Introductionmentioning
confidence: 99%